ANALYSIS OF MANUFACTURING FIRM OPERATIONAL MANAGEMENT - Ratnawita Ratnawita; Suryati Eko Putro; Muhammad Rozali (Jurnal Ekonomi, 2023)
The higher growth of companies results in increasingly fierce competition in every business sector. To be able to survive in competition and increase sales volume, companies must have a new and mature strategy. Of course, in an established company, increasing sales volume requires an operational strategy. This study focuses on examining the implementation of the operational management strategy of the manufacturing company PT Hanan Boga Rasa in terms of human resources, work design, measurement of working hours, project management, process strategy and quality control. This research also examines changes in the company before the Covid-19 pandemic and after.